Evaluating the Role of Digital Infrastructure and Labour Market Efficiency in Promoting Women’s Digital Entrepreneurship: A Comparative Study of Selected Asian Countries - Kumar, Prashant (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study investigates the role of digital infrastructure and labor market efficiency in fostering women’s digital entrepreneurship across five Asian countries India, China, Japan, Pakistan, and Russia. By leveraging secondary data from the World Bank’s Gender Data Portal (2000–2024) and conducting econometric analysis using unit root and cointegration tests (Johansen and Engle-Granger methods), the study identifies structural relationships in female labor force participation (FLF) and its link to digital inclusion. Findings reveal that while countries like China and Russia have achieved notable progress in women's digital economic participation due to policy support and internet access, others like India and Pakistan continue to face barriers such as digital gender divide, low digital literacy, and limited access to finance. The study concludes that digital entrepreneurship can be a transformative tool for women’s empowerment, but it requires coordinated policy efforts targeting digital infrastructure, financial inclusion, labor flexibility, and gender-sensitive innovation.